S2P2—the chloroplast-located intramembrane protease and its impact on the stoichiometry and functioning of the photosynthetic apparatus of A. thaliana - Ciesielska, Maria; Adamiec, Małgorzata; Luciński, Robert (Frontiers in Plant Science, 2024)
S2P2 is a nuclear-encoded protease, potentially located in chloroplasts, which belongs to the zinc-containing, intramembrane, site-2 protease (S2P) family. In A. thaliana cells, most of the S2P proteases are located within the chloroplasts, where they play an important role in the development of chloroplasts, maintaining proper stoichiometric relations between polypeptides building photosynthetic complexes and influencing the sensitivity of plants to photoinhibitory conditions. Among the known chloroplast S2P proteases, S2P2 protease is one of the least known. Its exact location within the chloroplast is not known, nor is anything known about its possible physiological functions. Therefore, we decided to investigate an intra-chloroplast localization and the possible physiological role of S2P2. To study the intra-chloroplast localization of S2P2, we used specific anti-S2P2 antibodies and highly purified chloroplast fractions containing envelope, stroma, and thylakoid proteins. To study the physiological role of the protease, we used two lines of insertion mutants lacking the S2P2 protease protein. Here, we present results demonstrating the thylakoid localization of S2P2. Moreover, we present experimental evidence indicating that the lack of S2P2 in A. thaliana chloroplasts leads to a significant decrease in the level of photosystem I and photosystem II core proteins: PsaB, PsbA, PsbD, and PsbC, as well as polypeptides building both the main light-harvesting antenna (LHC II), Lhcb1 and Lhcb2, as well as Lhcb4 and Lhcb5 polypeptides, constituting elements of the minor, peripheral antenna system. These changes are associated with a decrease in the number of PS II–LHC II supercomplexes. The consequence of these disorders is a greater sensitivity of s2p2 mutants to photoinhibition. The obtained results clearly indicate that the S2P2 protease is another thylakoid protein that plays an important role in the proper functioning of A. thaliana chloroplasts, especially in high-light-intensity conditions.